Wave nonlinear interaction effect on beam-plasma reciprocal influence - Buts, V.A.; Kovpik, O.F.; Kornilov, E.A. (Вопросы атомной науки и техники, 2005)
The authors have examined the oscillation excitation by an extensive nonrelativistic beam of electrons in the beamplasma discharge in the magnetic field when the beam power is about hundreds of kilowatts. It is demonstrated that lowfrequency (LF) ion waves from the range of the low hybrid (LH) resonance play the determinative role in maintaining the beam-plasma discharge. Excitation of such waves is stimulated by the nonlinear interaction between electron plasma oscillation modes of the decay type. The electromagnetic radiation emission from the discharge of pulses is stimulated by the above-mentioned nonlinear interaction, which also causes the wave stochasticity and stabilizes the beam instability.